A Vale em Moçambique: uma etnografia das relações entre brasileiros e moçambicanos no cotidiano dos megaprojetos - Rodrigues, Yssyssay D [UNESP] (2015)
This dissertation consists of an ethnographic focusing the relationship between Brazilian and Mozambican people in a context of the megaprojects developed by the mining company Vale in Mozambique, specifically The Moatize Coal Mine Project and The Nacala Corridor Project developed in Tete, Niassa and Nampula provinces, in the central and northern regions of the country. The research analysed the subjective impacts of the contact between the two groups of people within a delimited context, deepening the understanding of their practices and quotidian representations, using as analysis tools the debates about development, domination, racism and colonisation. Based on fieldwork and bibliographical research, the study aimed to understand the role of Brazil on Mozambican development project, analysing the relation of international cooperation between the two countries and observing the way the mentioned relationship can be effectuated under domination of neocolonialism in multiple aspects, especially what concerns private Brazilian projects developed in Mozambique. It was also observed the construction of racial ideologies in both countries, the way that Brazilian racism is practiced in Mozambique and the intrinsic connection between racism, the civilising project and colonialism in the scope of the already pointed relationships based in domination. The purpose being to analyse such relationships as complex processes, deconstructing the dichotomy dominated/dominator, giving priority to an intersectional approach to social differences borders; the research intends to problematize the analysed relations and, hence, contribute to overcome the identified questions, not only at a project level, but in a broader realm of relations between Brazil and Mozambique, and the PALOP in general